2020
DOI: 10.1002/aenm.202001005
|View full text |Cite
|
Sign up to set email alerts
|

3D Holey‐Graphene Architecture Expedites Ion Transport Kinetics to Push the OER Performance

Abstract: The electrochemical oxygen evolution reaction (OER) have been regarded as one of the most important process in a wide range of the above renewable-energy technologies. [6][7][8][9] However, OER is kinetically challenging, and highly desirable for effective electrocatalysts. Ir-and Rubased materials exhibit the highest activity for these electrochemical reactions, but these precious-metal catalysts cannot be largely used for clean energy because of their scarcity on earth and high cost. [10,11] Therefore, nonpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Figure 6 b shows the Tafel slope value derived from the LSV curve, and the Tafel slope shows the unique properties of the electrochemical catalytic electrode. The Tafel slope is the value of the electrode potential required when 10-fold electrons flow, and it is reported that the lower this value, the better the water-oxidation kinetics [ 40 ]. In Figure 6 b, the Tafel slope of GF showed 325 mV dec −1 , and the Ni 0.75 Cu 0.25 Co 2 O 4 /GF electrode, which expressed the lowest electrode potential in the LSV curve, also showed the lowest Tafel slope with 119 mV dec −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 b shows the Tafel slope value derived from the LSV curve, and the Tafel slope shows the unique properties of the electrochemical catalytic electrode. The Tafel slope is the value of the electrode potential required when 10-fold electrons flow, and it is reported that the lower this value, the better the water-oxidation kinetics [ 40 ]. In Figure 6 b, the Tafel slope of GF showed 325 mV dec −1 , and the Ni 0.75 Cu 0.25 Co 2 O 4 /GF electrode, which expressed the lowest electrode potential in the LSV curve, also showed the lowest Tafel slope with 119 mV dec −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The XPS further analyzed the elemental composition and chemical states of the 5% NiO/CdS sample. Two peaks appear at 853.9 and 872.2 eV in the Ni 2p spectrum (Figure 3A), corresponding to the binding energies of Ni 2+ 2p 3/2 , and 2p 1/2 ; the peaks at 860.1 and 878.8 eV could be attributed to the satellite peaks (Yang et al, 2019;Wu et al, 2020). As shown in Figure 3B, the peak located at 530.6 eV could be attributed to the lattice oxygen of NiO (Wang et al, 2010;Liu et al, 2012;Hu et al, 2018).…”
Section: Synthesis and Characterizationmentioning
confidence: 91%
“…The B-V Equation (Equation (4)) can be simplified to the form of Equation (6), which is originally put forward by Tafel as an empirical formula, in which a refers to the overpotential at a current density of 1 mA/cm 2 and b is the Tafel slope. η = a + blog(j)…”
Section: Tafel Slopementioning
confidence: 99%
“…Restricted by the slow four-electron transfer process [6][7][8], OER is more likely to block the total reaction than HER, which is merely a two-electron reaction [9]. The sluggish kinetic process of OER requires a higher potential to cross the energy barrier, thus greatly increasing the cost of the reaction.…”
Section: Introductionmentioning
confidence: 99%